Can't We Just Use Computers? Initial Efforts on Technology-Enhanced Learning of Operations Research in a Philippine University - Hao, Lester (Archīum Ateneo, 2024)
Operations Research (OR) is a required course in any applied math program in the Philippines. It involves complex and computation-heavy algorithms to guide and improve decision-making in organizations and relevant contexts. Despite the advent of software that have automated the computations or the implementation of algorithms, the teaching and learning of OR may still be rife with procedures being performed manually by hand. In this paper, we report on our initial progress on a research project that aims to revise the OR syllabi in one Philippine university, by integrating more technological tools in the teaching and learning of OR for undergraduate and graduate students. We present the study’s conceptual underpinnings and methodology, and discuss some initial results on the syllabi revisions.